Less is more! Low amount of Fusobacterium nucleatum supports macrophage-mediated trophoblast functions in vitro - Einenkel, Rebekka; Ehrhardt, Jens; Zygmunt, Marek; Muzzio, Damián Oscar (Frontiers in Immunology, 2024)
F. nucleatum, involved in carcinogenesis of colon carcinomas, has been described as part of the commensal flora of the female upper reproductive tract. Although its contribution to destructive inflammatory processes is well described, its role as commensal uterine bacteria has not been thoroughly investigated. Since carcinogenesis shares similar mechanisms with early pregnancy development (including proliferation, invasion, blood supply and the induction of tolerance), these mechanisms induced by F. nucleatum could play a role in early pregnancy. Additionally, implantation and placentation require a well-balanced immune activation, which might be suitably managed by the presence of a limited amount of bacteria or bacterial residues. We assessed the effect of inactivated F. nucleatum on macrophage-trophoblast interactions.Monocytic cells (THP-1) were polarized into M1, M2a or M2c macrophages by IFN-γ, IL-4 or TGFβ, respectively, and subsequently treated with inactivated fusobacteria (bacteria:macrophage ratio of 0.1 and 1). Direct effects on macrophages were assessed by viability assay, flow cytometry (antigen presentation molecules and cytokines), qPCR (cytokine expression), in-cell Western (HIF and P-NF-κB) and ELISA (VEGF secretion). The function of first trimester extravillous trophoblast cells (HTR-8/SVneo) in response to macrophage-conditioned medium was microscopically assessed by migration (scratch assay), invasion (sprouting assay) and tube formation. Underlying molecular changes were investigated by ELISA (VEGF secretion) and qPCR (matrix-degrading factors and regulators).Inflammation-primed macrophages (M1) as well as high bacterial amounts increased pro-inflammatory NF-κB expression and inflammatory responses. Subsequently, trophoblast functions were impaired. In contrast, low bacterial stimulation caused an increased HIF activation and subsequent VEGF-A secretion in M2c macrophages. Accordingly, there was an increase of trophoblast tube formation.Our results suggest that a low-mass endometrial/decidual microbiome can be tolerated and while it supports implantation and further pregnancy processes.